You are on page 1of 15

Derivation of Local Volatility

by Fabrice Douglas Rouah

www.FRouah.com
www.Volopta.com
The derivation of local volatility is outlined in many papers and textbooks
(such as the one by Jim Gatheral [1]), but in the derivations many steps are left
out. In this Note we provide two derivations of local volatility.
1. The derivation by Dupire [2] that uses the Fokker-Planck equation.
2. The derivation by Derman et al. [3] of local volatility as a conditional
expectation.
We also present the derivation of local volatility from Black-Scholes implied
volatility, outlined in [1]. We will derive the following three equations that
involve local volatility o = o(o
t
, t) or local variance
L
= o
2
.
1. The Dupire equation in its most general form (appears in [1] on page 9)
0C
0T
=
1
2
o
2
1
2
0
2
C
01
2
+ (r
T

T
)
_
C 1
0C
01
_
. (1)
2. The equation by Derman et al. [3] for local volatility as a conditional
expected value (appears with
T
= 0 in [3])
0C
0T
= 1(r
T

T
)
0C
01

T
C +
1
2
1
2
1
_
o
2
T
[o
T
= 1

0
2
C
01
2
. (2)
3. Local volatility as a function of Black-Scholes implied volatility, =
(1, T) (appears in [1]) expressed here as the local variance
L

L
=
@w
@T
_
1
y
w
@w
@y
+
1
2
@
2
w
@y
2
+
1
4
_

1
4

1
w
+
y
2
w
__
@w
@y
_
2
_. (3)
where n = (1, T)
2
T is the Black-Scholes total implied variance and j =
ln
K
F
T
where 1
T
= exp
_
_
T
0
j
t
dt
_
is the forward price with j
t
= r
t

t
(risk free
rate minus dividend yield). Alternatively, local volatility can also be expressed
in terms of as

2
+ 2T
_
@
@T
+ (r
T

T
) 1
@
@K

_
1 +
Ky

@
@K
_
2
+ 1T
_
@
@K

1
4
1T
_
@
@K
_
2
+ 1
@
2

@K
2
_
.
Solving for the local variance in Equation (1), we obtain
o
2
= o (1, T)
2
=
@C
@T
(r
T

T
)
_
C 1
@C
@K
_
1
2
1
2
@
2
C
@K
2
. (4)
1
If we set the risk-free rate r
T
and the dividend yield
T
each equal to zero,
Equations (1) and (2) can each be solved to yield the same equation involving
local volatility, namely
o
2
= o (1, T)
2
=
@C
@T
1
2
1
2
@
2
C
@K
2
. (5)
The local volatility is then
L
=
_
o
2
(1, T). In this Note the derivation of
these equations are all explained in detail.
1 Local Volatility Model for the Underlying
The underlying o
t
follows the process
do
t
= j
t
o
t
dt + o(o
t
, t)o
t
d\
t
(6)
= (r
t

t
) o
t
dt + o(o
t
, t)o
t
d\
t
.
We sometimes drop the subscript and write do = jodt + ood\ where o =
o(o
t
, t). We need the following preliminaries:
Discount factor 1(t, T) = exp
_

_
T
t
r
s
d:
_
.
Fokker-Planck equation. Denote by )(o
t
, t) the probability density func-
tion of the underlying price o
t
at time t. Then ) satises the equation
0)
0t
=
0
0o
[jo)(o, t)] +
1
2
0
2
0o
2
_
o
2
o
2
)(o, t)

. (7)
Time-t price of European call with strike 1, denoted C = C(o
t
, 1)
C = 1(t, T)1
_
(o
T
1)
+

(8)
= 1(t, T)1
_
(o
T
1)1
(S
T
>K)

= 1(t, T)
_
1
K
(o
T
1))(o, T)do.
where 1
(S
T
>K)
is the Heaviside function and where 1 [] = 1 [[T
t
]. In the
all the integrals in this Note, since the expectations are taken for the underlying
price at t = T it is understood that o = o
T
, )(o, T) = )(o
T
, T) and do = do
T
.
We sometimes omit the subscript for notational convenience.
2 Derivation of the General Dupire Equation (1)
2.1 Required Derivatives
We need the following derivatives of the call C(o
t
, t).
2
First derivative with respect to strike
0C
01
= 1(t, T)
_
1
K
0
01
(o
T
1))(o, T)do (9)
= 1(t, T)
_
1
K
)(o, T)do.
Second derivative with respect to strike
0
2
C
01
2
= 1(t, T) [)(o, T)]
S=1
S=K
(10)
= 1(t, T))(1, T).
We have assumed that lim
S!1
)(o, T) = 0.
First derivative with respect to maturityuse the chain rule
0C
0T
=
0C
0T
1(t, T)
_
1
K
(o
T
1))(o, T)do + (11)
1(t, T)
_
1
K
(o
T
1)
0
0T
[)(o, T)] do.
Note that
@P
@T
= r
T
1(t, T) so we can write (11)
0C
0T
= r
T
C + 1(t, T)
_
1
K
(o
T
1)
0
0T
[)(o, T)] do. (12)
2.2 Main Equation
In Equation (12) substitute the Fokker-Planck equation (7) for
@f
@t
at t = T
0C
0T
+ r
T
C = 1(t, T)
_
1
K
(o
T
1) (13)
_

0
0o
[j
T
o)(o, T)] +
1
2
0
2
0o
2
_
o
2
o
2
)(o, T)

_
do.
This is the main equation we need because it is from this equation that the
Dupire local volatility is derived. In Equation (13) have two integrals to evaluate
1
1
= j
T
_
1
K
(o
T
1)
0
0o
[o)(o, T)] do, (14)
1
2
=
_
1
K
(o
T
1)
0
2
0o
2
_
o
2
o
2
)(o, T)

do.
Before evaluating these two integrals we need the following two identities.
3
2.3 Two Useful Identities
2.3.1 First Identity
From the call price Equation (8), we obtain
C
1(t, T)
=
_
1
K
(o
T
1))(o, T)do (15)
=
_
1
K
o
T
)(o, T)do 1
_
1
K
)(o, T)do.
From the expression for
@C
@K
in Equation (9) we obtain
_
1
K
)(o, T)do =
1
1(t, T)
0C
01
.
Substitute back into Equation (15) and re-arrange terms to obtain the rst
identity
_
1
K
o
T
)(o, T)do =
C
1(t, T)

1
1(t, T)
0C
01
. (16)
2.3.2 Second Identity
We use the expression for
@
2
C
@K
2
in Equation (10) to obtain the second identity
)(1, T) =
1
1(t, T)
0
2
C
01
2
. (17)
2.4 Evaluating the Integrals
We can now evaluate the integrals 1
1
and 1
2
dened in Equation (14).
2.4.1 First integral
Use integration by parts with n = o
T
1, n
0
= 1,
0
=
@
@S
[o)(o, T)] , =
o)(o, T)
1
1
= [j
T
(o
T
1)o
T
)(o, T)]
S=1
S=K
j
T
_
1
K
o)(o, T)do
= [0 0] j
T
_
1
K
o)(o, T)do.
We have assumed lim
S!1
(o 1)o)(o, T) = 0. Substitute the rst identity (16)
to obtain the rst integral 1
1
1
1
=
j
T
C
1(t, T)
+
j
T
1
1(t, T)
0C
01
. (18)
4
2.4.2 Second integral
Use integration by parts with n = o
T
1, n
0
= 1,
0
=
@
2
@S
2
_
o
2
o
2
)(o, T)

, =
@
@S
_
o
2
o
2
)(o, T)

1
2
=
_
(o
T
1)
0
0o
_
o
2
o
2
)(o, T)
_
_
S=1
S=K

_
1
K
0
0o
_
o
2
o
2
)(o, T)

do
= [0 0]
_
o
2
o
2
)(o, T)

S=1
S=K
= o
2
1
2
)(1, T)
where o
2
= o(1, T)
2
. We have assumed that lim
S!1
@
@S
_
o
2
o
2
)(o, T)
_
= 0.
Substitute the second identity (17) for )(1, T) to obtain the second integral 1
2
1
2
=
o
2
1
2
1(t, T)
0
2
C
01
2
. (19)
2.5 Obtaining the Dupire Equation
We can now evaluate the main Equation (13) which we write as
0C
0T
+ r
T
C = 1(t, T)
_
1
1
+
1
2
1
2
_
.
Substitute for 1
1
from Equation (18) and for 1
2
from Equation (19)
0C
0T
+ r
T
C = j
T
C j
T
1
0C
01
+
1
2
o
2
1
2
0
2
C
01
2
Substitute for j
T
= r
T

T
(risk free rate minus dividend yield) to obtain the
Dupire equation (1)
0C
0T
=
1
2
o
2
1
2
0
2
C
01
2
+ (r
T

T
)
_
C 1
0C
01
_
.
Solve for o
2
= o(1, T)
2
to obtain the Dupire local variance in its general form
o(1, T)
2
=
@C
@T
+
T
C + (r
T

K
)1
@C
@K
1
2
1
2
@
2
C
@K
2
Dupire [2] assumes zero interest rates and zero dividend yield. Hence r
T
=

T
= 0 so that the underlying process is do
t
= o(o
t
, t)o
t
d\
t
. We obtain
o(1, T)
2
=
@C
@T
1
2
1
2
@
2
C
@K
2
.
which is Equation (5).
5
3 Derivation of Local Volatility as an Expected
Value, Equation (2)
We need the following preliminaries, all of which are easy to show
@
@S
(o 1)
+
= 1
(S>K)
@
@S
1
(S>K)
= c(o 1)
@
@K
(o 1)
+
= 1
(S>K)
@
@K
1
(S>K)
= c(o 1)
@C
@K
= 1(t, T)1
_
1
(S>K)

@
2
C
@K
2
= 1(t, T)1 [c(o 1)]
In the table, c() denotes the Dirac delta function. Now dene the function
)(o
T
, T) as
)(o
T
, T) = 1(t, T)(o
T
1)
+
.
Recall the process for o
t
is given by Equation (6). By Itos Lemma, ) follows
the process
d) =
_
0)
0T
+ j
T
o
T
0)
0o
T
+
1
2
o
2
T
o
T
0
2
)
0o
2
T
_
dT +
_
o
T
o
T
0)
0o
T
_
d\
T
. (20)
Now the partial derivatives are
0)
0T
= r
T
1(t, T)(o
T
1)
+
,
0)
0o
T
= 1(t, T)1
(S
T
>K)
,
0
2
)
0o
2
T
= 1(t, T)c (o
T
1) .
Substitute them into Equation (20)
d) = 1(t, T) (21)
_
r
T
(o
T
1)
+
+ j
T
o
T
1
(S
T
>K)
+
1
2
o
2
T
o
2
T
c(o
T
1)
_
dT
+1(t, T)
_
o
T
o
T
1
(S
T
>K)

d\
T
Consider the rst two terms of (21), which can be written as
r
T
(o
T
1)
+
+ j
T
o
T
1
(S
T
>K)
= r
T
(o
T
1)1
(S
T
>K)
+ j
T
o
T
1
(S
T
>K)
= r
T
11
(S
T
>K)

T
o
T
1
(S
T
>K)
.
When we take the expected value of Equation (21), the stochastic term drops
out since 1 [d\
T
] = 0. Hence we can write the expected value of (21) as
dC = 1 [d)] (22)
= 1(t, T)1
_
r
T
11
(S
T
>K)

T
o
T
1
(S
T
>K)
+
1
2
o
2
T
o
2
T
c(o
T
1)
_
dT
6
so that
dC
dT
= 1(t, T)1
_
r
T
11
(S
T
>K)

T
o
T
1
(S
T
>K)
+
1
2
o
2
T
o
2
T
c(o
T
1)
_
. (23)
Using the second line in Equation (8), we can write
1(t, T)1
_
o
T
1
(S
T
>K)

= C + 11(t, T)1
_
1
(S
T
>K)

dC
dT
= 11(t, T)r
T
1[1
(S
T
>K)
]
T
_
C + 11(t, T)1
_
1
(S
T
>K)
_
(24)
+
1
2
1(t, T)1
_
o
2
T
o
2
T
c(o
T
1)

= 1(r
T

T
)
0C
01

T
C +
1
2
1(t, T)1
_
o
2
T
o
2
T
c(o
T
1)

where we have substituted

@C
@K
for 1(t, T)1[1
(S
T
>K)
]. The last term in the
last line of Equation (24) can be written
1
2
1(t, T)1
_
o
2
T
o
2
T
c(o
T
1)

=
1
2
1(t, T)1
_
o
2
T
o
2
T
[o
T
= 1

1[c(o
T
1)]
=
1
2
1(t, T)1
_
o
2
T
[o
T
= 1

1
2
1[c(o
T
1)]
=
1
2
1
_
o
2
T
[o
T
= 1

1
2
0
2
C
01
2
where we have substituted
@
2
C
@K
2
for 1(t, T)1[c(o
T
1)]. We obtain the nal
result, Equation (2)
0C
0T
= 1(r
T

T
)
0C
01

T
C +
1
2
1
2
1
_
o
2
T
[o
T
= 1

0
2
C
01
2
.
When r
T
=
T
= 0 we can re-arrange the result to obtain
1
_
o
2
T
[o
T
= 1

=
@C
@T
1
2
1
2
@
2
C
@K
2
which, again, is Equation (5). Hence when the dividend and interest rate are
both zero, the derivation of local volatility using Dupires approach and the
derivation using conditional expectation produce the same result.
4 Derivation of Local Volatility From Implied
Volatility, Equation (3)
To express local volatility in terms of implied volatility, we need the three deriv-
atives
@C
@T
,
@C
@K
, and
@
2
C
@K
2
that appear in Equation (1), but expressed in terms of
7
implied volatility. Following Gatheral [1] we dene the log-moneyness
j = ln
1
1
T
where 1
T
= o
0
exp
_
_
T
0
j
t
dt
_
is the forward price (j
t
= r
t

t
, risk free rate
minus dividend yield) and 1 is the strike price, and the "total" Black-Scholes
implied variance
n = (1, T)
2
T
where (1, T) is the implied volatility. The Black-Scholes call price can then
be written as
C
BS
(o
0
, 1, (1, T) , T) = C
BS
(o
0
, 1
T
c
y
, n, T) (25)
= 1
T
(d
1
) c
y
(d
2
)
where
d
1
=
ln
S0
K
+
_
T
0
(r
t

t
) dt +
w
2
_
n
= jn

1
2
+
1
2
n
1
2
(26)
and d
2
= d
1

_
n = jn

1
2

1
2
n
1
2
.
4.1 The Reparameterized Local Volatility Function
To express the local volatility Equation (1) in terms of j, we note that the
market call price is
C(o
0
, 1, T) = C(o
0
, 1
T
c
y
, T)
and we take derivatives. The rst derivative we need is, by the chain rule
0C
0j
=
0C
01
01
0j
=
0C
01
1. (27)
The second derivative we need is
0
2
C
0j
2
=
0
0j
_
0C
01
_
1 +
0C
01
01
0j
(28)
=
0
2
C
01
2
1
2
+
0C
0j
,
since by the chain rule
@A
@y
=
@A
@K
@K
@y
, so that
@
@y
_
@C
@K
_
=
@
2
C
@K
2
@K
@y
=
@
2
C
@K
2
1. The
third derivative we need is
0C
0T
=
0C
0T
+
0C
01
01
0T
(29)
=
0C
0T
+
0C
01
1j
T
=
0C
0T
+
0C
0j
j
T
8
since 1 = o
0
exp
_
_
T
0
j
t
dt + j
_
so that
@K
@T
= 1j
T
. Equation (28) implies
that
0
2
C
01
2
1
2
=
0
2
C
0j
2

0C
0j
.
Now we substitute into Equation (1), reproduced here for convenience
0C
0T
=
1
2
o
2
1
2
0
2
C
01
2
+ j
T
_
C 1
0C
01
_
0C
0T

0C
0j
j
T
=
1
2
o
2
_
0
2
C
0j
2

0C
0j
_
+ j
T
_
C
0C
0j
_
which simplies to
0C
0T
=

L
2
_
0
2
C
0j
2

0C
0j
_
+ j
T
C (30)
where
L
= o
2
(1, T) is the local variance. This is Equation (1.8) of Gatheral
[1].
4.2 Three Useful Identities
Before expression the local volatility Equation (1) in terms of implied volatility,
we rst derive three identities used by Gatheral [1] that help in this regard. We
use the fact that the derivatives of the standard normal cdf and pdf are, using
the chain rule,
0
(r) = :(r)r
0
and :
0
(r) = r:(r)r
0
. We also use the relation
:(d
1
) =
1
_
2
c

1
2
(d2+
p
w)
2
=
1
_
2
c

1
2
(d
2
2
+2d2
p
w+w)
= :(d
2
)c
d2
p
w
1
2
w
= :(d
2
)c
y
.
From Equation (25) the rst derivative with respect to n is
0C
BS
0n
= 1
T
[:(d
1
)d
1w
c
y
:(d
2
)d
2w
]
= 1
T
_
:(d
2
)c
y
_
d
2w
+
1
2
n

1
2
_
c
y
:(d
2
)d
2w
_
=
1
2
1
T
c
y
_
:(d
2
)n

1
2
_
9
where d
1w
is the rst derivative of d
1
with respect to n and similarly for d
2
.
The second derivative is
0
2
C
BS
0n
2
=
1
2
1
T
c
y
_
:(d
2
)d
2
d
2w
n

1
2

1
2
:(d
2
)n

3
2
_
(31)
=
1
2
1
T
c
y
:(d
2
)n

1
2
_
d
2
d
2w

1
2
n
1
_
=
0C
BS
0n
__
jn

1
2
+
1
2
n
1
2
__
1
2
jn

3
2

1
4
n

1
2
_

1
2
n
1
_
=
0C
BS
0n
_

1
8

1
2n
+
j
2
2n
2
_
.
This is the rst identity we need. The second identity we need is
0
2
C
BS
0n0j
=
1
2
1
T
n

1
2
0
0j
[c
y
:(d
2
)] (32)
=
1
2
1
T
n

1
2
[c
y
:(d
2
) c
y
:(d
2
)d
2
d
2y
]
=
0C
BS
0n
[1 d
2
d
2y
]
=
0C
BS
0n
_
1
2

j
n
_
where d
2y
= n

1
2
is the rst derivative of d
2
with respect to j. To obtain the
third identity, consider the derivative
0C
BS
0j
= 1
T
[:(d
1
)d
1y
c
y
(d
2
) c
y
:(d
2
)d
2y
]
= 1
T
c
y
[:(d
2
)d
1y
(d
2
) :(d
2
)d
2y
]
= 1
T
c
y
(d
2
).
The third identity we need is
0
2
C
BS
0j
2
= 1
T
[c
y
(d
2
) + c
y
:(d
2
)d
2y
] (33)
= 1
T
c
y
(d
2
) + 1
T
c
y
:(d
2
)n

1
2
=
0C
BS
0j
+ 2
0C
BS
0n
.
We are now ready for the main derivation of this section.
4.3 Local Volatility in Terms of Implied Volatility
We note that when the market price C(o
0
, 1, T) is equal to the Black-Scholes
price with the implied volatility (1, T) as the input to volatility
C(o
0
, 1, T) = C
BS
(o
0
, 1, (1, T), T). (34)
10
We can also reparameterize the Black-Scholes price in terms of the total implied
volatility n = (1, T)
2
T and 1 = 1
T
c
y
. Since n depends on 1 and 1 depends
on j, we have that n = n(j) and we can write
C(o
0
, 1, T) = C
BS
(o
0
, 1
T
c
y
, n(j), T). (35)
We need derivatives of the market call price C(o
0
, 1, T) in terms of the Black-
Scholes call price C
BS
(o
0
, 1
T
c
y
, n(j), T). From Equation (35), the rst deriv-
ative we need is
0C
0j
=
0C
BS
0j
+
0C
BS
0n
0n
0j
(36)
= a(n, j) + /(n, j)c(j).
It is easier to visualize the second derivative we need,
@
2
C
@y
2
, when we express the
partials in
@C
@y
as a, /, and c.
0
2
C
0j
2
=
0a
0j
+
0a
0n
0n
0j
+ /(n, j)
0c
0j
+
_
0/
0j
+
0/
0n
0n
0j
_
c(j) (37)
=
0
2
C
BS
0j
2
+
0
2
C
BS
0j0n
0n
0j
+
0C
BS
0n
0
2
n
0j
2
+
_
0
2
C
BS
0n0j
+
0
2
C
BS
0n
2
0n
0j
_
0n
0j
=
0
2
C
BS
0j
2
+ 2
0
2
C
BS
0j0n
0n
0j
+
0C
BS
0n
0
2
n
0j
2
+
0
2
C
BS
0n
2
_
0n
0j
_
2
.
The third derivative we need is
0C
0T
=
0C
BS
0T
+
0C
BS
0n
0n
0T
(38)
= j
T
C +
0C
BS
0n
0n
0T
.
Gatheral explains that the second equality follows because the only explicit
dependence of C
BS
on T is through the forward price 1
T
, even though C
BS
depends implicitly on T through j and n. The reparameterized Dupire equation
(30) is reproduced here for convenience
0C
0T
=

L
2
_
0
2
C
0j
2

0C
0j
_
+ j
T
C.
We substitute for
@C
@T
,
@
2
C
@y
2
, and
@C
@y
from Equations (38), (37), and (36) respec-
tively and cancel j
T
C from both sides to obtain
0C
BS
0n
0n
0T
=

L
2
_
0
2
C
BS
0j
2
+ 2
0
2
C
BS
0j0n
0n
0j
+
0C
BS
0n
0
2
n
0j
2
+
0
2
C
BS
0n
2
_
0n
0j
_
2

0C
BS
0j
+
0C
BS
0n
0n
0j
_
. (39)
11
Now substitute for
@
2
C
BS
@w
2
,
@
2
C
BS
@w@y
, and
@
2
C
BS
@y
2
from the identities in Equations
(31), (32), and (33) respectively, the idea being to end up with terms involving
@C
BS
@w
on the right hand side of Equation (39) that can be factored out.
0C
BS
0n
0n
0T
=

L
2
0C
BS
0n
_
2 + 2
_
1
2

j
n
_
0n
0j
+
_

1
8

1
2n
+
j
2
2n
__
0n
0j
_
2
+
0
2
n
0j
2

0n
0j
_
.
Remove the factor
@C
BS
@w
from both sides and simplify to obtain
0n
0T
=
L
_
1
j
n
0n
0j
+
1
2
0
2
n
0j
2
+
1
4
_

1
4

1
n
+
j
2
n
__
0n
0j
_
2
_
.
Solve for
L
to obtain the nal expression for the local volatility expressed in
terms of implied volatility n = (1, T)
2
T and the log-moneyness j = ln
K
F
T

L
=
@w
@T
_
1
y
w
@w
@y
+
1
2
@
2
w
@y
2
+
1
4
_

1
4

1
w
+
y
2
w
__
@w
@y
_
2
_.
4.4 Alternate Derivation
In this derivation we express the derivatives
@C
@K
,
@
2
C
@K
2
, and
@C
@T
in the Dupire
equation (1) in terms of j and n = n(j), but we substitute these derivatives
directly in Equation (1) rather than in (30). This means that we take derivatives
with respect to 1 and T, rather than with j and T. Recall that from Equation
(35), the market call price is equal to the Black-Scholes call price with implied
volatility as input
C(o
0
, 1, T) = C
BS
(o
0
, 1
T
c
y
, n(j), T).
Recall also that from Equation (25) the Black-Scholes call price reparameterized
in terms of j and n is
C
BS
(o
0
, 1
T
c
y
, n(j), T) = 1
T
(d
1
) c
y
(d
2
)
where d
1
is given in Equation (26), and where d
2
= d
1

_
n. The rst derivative
we need is
0C
01
=
0C
BS
0j
0j
01
+
0C
BS
0n
0n
01
(40)
=
1
1
0C
BS
0j
+
0C
BS
0n
0n
01
.
12
The second derivative is
0
2
C
01
2
=
1
1
2
0C
BS
0j
+
1
1
0
01
_
0C
BS
0j
_
. (41)
+
0
01
_
0C
BS
0n
_
0n
01
+
0C
BS
0n
0
2
n
01
2
Let =
@C
@y
for notational convenience. Then
@
@K
_
@C
@y
_
=
@A
@K
and
0
01
_
0C
BS
0j
_
=
0
01
(42)
=
0
0j
0j
01
+
0
0n
0n
01
=
0
2
C
BS
0j
2
1
1
+
0
2
C
BS
0j0n
0n
01
.
Similarly
0
01
_
0C
BS
0n
_
=
0
2
C
BS
0j0n
1
1
+
0
2
C
BS
0n
2
0n
01
. (43)
Substituting Equations (42) and (43) into Equation (41) produces
0
2
C
01
2
=
1
1
2
0C
BS
0j
+
1
1
_
0
2
C
BS
0j
2
1
1
+
0
2
C
BS
0j0n
0n
01
_
(44)
+
_
0
2
C
BS
0j0n
1
1
+
0
2
C
BS
0n
2
0n
01
_
0n
01
+
0C
BS
0n
0
2
n
01
2
=
1
1
2
_
0
2
C
BS
0j
2

0C
BS
0j
_
+
2
1
0
2
C
BS
0j0n
0n
01
+
0
2
C
BS
0n
2
_
0n
01
_
2
+
0C
BS
0n
0
2
n
01
2
.
The third derivative we need is
0C
0T
=
0C
BS
0T
+
0C
BS
0j
0j
0T
+
0C
BS
0n
0n
0T
(45)
= j
T
C
BS
+
0C
BS
0j
j
T
+
0C
BS
0n
0n
0T
,
again using the fact that
@C
BS
@T
depends explicitly on T only through 1
T
. Now
substitute for
@C
@K
,
@
2
C
@K
2
, and
@C
@T
from Equations (40), (44), and (45) respectively
into Equation (4) for Dupire local variance, reproduced here for convenience.
o
2
=
@C
@T
j
T
_
C
BS
1
@C
@K

1
2
1
2
@
2
C
@K
2
.
13
We obtain, after applying the three useful identities in Section 4.2,
o
2
=
j
T
C
BS
+
@C
BS
@y
j
T
+
@C
BS
@w
@w
@T
j
T
_
C
BS
1
_
1
K
@C
BS
@y
+
@C
BS
@w
@w
@K
__
1
2
1
2
_
1
K
2
_
@
2
C
BS
@y
2

@C
BS
@y
_
+
2
K
@
2
C
BS
@y@w
@w
@K
+
@
2
C
BS
@w
2
_
@w
@K
_
2
+
@C
BS
@w
@
2
w
@K
2
_.
Applying the three useful identities in Section 4.2 allows the term
@C
BS
@w
to be
factored out of the numerator and denominator. The last equation becomes
o
2
=
_
@w
@T
+ j
T
1
@w
@K

1
2
1
2
_
2
K
2
+
2
K
_
1
2

y
w
_
@w
@K
+
_

1
8

1
2w
+
y
2
2w
2
_
_
@w
@K
_
2
+
@
2
w
@K
2
_. (46)
Equation (46) can be simplied by considering deriving the partial derivatives
of the Black-Scholes total implied variance, n = (1, T)
2
T. We have
@w
@T
=
2T
@
@T
+
2
,
@w
@K
= 2T
@
@K
, and
@
2
w
@K
2
= 2T
_
_
@
@K
_
2
+
@
2

@K
2
_
. Substitute into
Equation (46). The numerator in Equation (46) becomes

2
+ 2T
_
0
0T
+ j
T
1
0
01
_
(47)
and the denominator becomes
1 + 21T
_
1
2

j
n
_
0
01
+ 21
2

2
T
2
_

1
8

1
2n
+
j
2
2n
2
__
0
01
_
2
+1
2
T
_
_
0
01
_
2
+
0
2

01
2
_
.
Replacing n with
2
T everywhere in the denominator produces
1 + 21T
_
1
2

j

2
T
_
0
01
+ 21
2

2
T
2
_

1
8

1
2
2
T
+
j
2
2
4
T
2
__
0
01
_
2
+1
2
T
_
_
0
01
_
2
+
0
2

01
2
_
= 1 + 1T
0
01

21j

0
01

1
2

2
T
2
4
_
0
01
_
2
+
1
2
j
2

2
_
0
01
_
2
+1
2
T
0
2

01
2
=
_
1
1j

0
01
_
2
+
_
1 2
1j

0
01
+
_
1j

0
01
_
2
_
. (48)
Substituting the numerator in (47) and the denominator in (48) back to Equa-
tion (46), we obtain

2
+ 2T
_
@
@T
+ j
T
1
@
@K
_
_
1 +
Ky

@
@K
_
2
+ 1T
_
@
@K

1
4
1T
_
@
@K
_
2
+ 1
@
2

@K
2
_
14